Equipment modification can enhance skill learning in young field hockey players - Brocken, J. E. A.; van der Kamp, J.; Lenoir, M.; Savelsbergh, G. J. P. (International Journal of Sports Science & Coaching, 2020)
The aim of the study was to investigate whether performance of children can be improved by training with modified equipment that challenges movement execution. For that purpose, young field hockey players practiced with a modified and a regular hockey ball. The modified hockey ball enforces more variable movement execution during practice by rolling less predictably than a regular hockey ball and, thus, challenges the players` stick-ball control. Two groups of 7- to 9-year old children, with 0 to 4 years of experience, participated in a crossover-design, in which they either received four training sessions with the modified ball followed by four training sessions with the regular ball or vice versa. In a pretest, intermediate test (i.e. following the first four training sessions) and a posttest, the participants dribbled an obstacle parcours with a regular ball. Results show that practice with the modified ball led to greater performance improvement than the intervention with the regular hockey ball. This performance improvement, however, was not predicted by experience and/or initial skill (i.e. pretest score). The findings indicate that by using modified equipment, sport trainers and physical education teachers can, presumably through enhancement of movement variability during practice, stimulate skill acquisition in young children.